Material selection of natural fibre using a grey relational analysis (GRA) approach - Maidin, N. A.; Mohd Sapuan, S.; Mohammad Taha, M.; Mohamed Yusoff, M. Z. (College of Natural Resources, North Carolina State University, 2022)
Numerous situations in daily life necessitate a decision. Several of them entail selecting the best option from a number of available options. In many such cases, no single solution is optimal for all of the performance characteristics. This study proposes using grey relational analysis (GRA), a multiple criteria decision making (MCDM) method, to solve this problem. Material selection is vital in designing and developing products, especially for composites materials requiring special attention. The substitution of conventional materials with natural fibres as base material is commonly practised due to high material consumption in mass-producing plastic components that could harm the environment. Therefore, in this work, natural fibres were chosen as composite reinforcement in the design of cyclist helmets. This approach was used to evaluate the right natural fibre and is able to fulfill the needs of consumers and the environment. From the results, the GRA method was utilised and revealed that pineapple was the best top ranking natural fibre with a grade of 0.5687, followed closely by bamboo with a grade of 0.5678, and abaca with a grade of 0.4966. Error analysis was performed to increase the confidence level of the results obtained.